The strategic trajectory of artificial intelligence in Qatar’s healthcare sector: a model for UN Sustainable Development Goal 9 - Ismail, Mohamed A. (Frontiers in Artificial Intelligence, 2026)
This narrative review is first of its kind to strategically position AI and healthcare in the Qatari state under the broad framework of QNV-2030. The review highlights Qatar’s forward-looking digital infrastructure upon which its AI initiatives are being built. The paper lists several innovative clinical process developments such as precision medicine and AI-based diagnostics. Furthermore, it analyzes the country’s strong ethical and regulatory frameworks underpinning AI adoption, including aspects related to privacy and security. While these aspects are positive, the review identifies areas of concern wherein improvements may be effected: a deeper critical analysis of implementation challenges, greater integration of empirical evidence, and strategies for human capital development beyond mere upskilling. This paper serves as an exemplary case study, demonstrating how a nation can strategically align its top-down initiatives, digital infrastructure investments, and forward-looking regulatory environment with the United Nations Sustainable Development Goal 9 (SDG 9), which focuses on Industry, Innovation, and Infrastructure.